INTERNATIONAL COLLABORATION PROGRAM: EDUCATIONAL GAME ACTIVITIES TO ENHANCE STUDENTS' CREATIVITY, TOGETHERNESS, AND LEARNING ENTHUSIASM AT SEKOLAH KEBANGSAAN TANJUNG SURAT, JOHOR, MALAYSIA - Harahap, Dahrul Aman; Yesa, Hesti Desba; Gaol, Lestari Herlina Lumban; Mokerje, Nadya Febriani; Utama, Yolanda Sa'ad; Ardhana, Alzeyna Dwilovita; Putra, Sulfanow; Dewi, Hanindianti; Borgias, Frans; Ridho Harahap, Rasyid; Wibowo, Agung Edy; Harefa, Selamat Kristian; Wibowo, Edwin Agung; Hasibuan, Rahman (RADJA PUBLIKA, 2025)
The international collaboration program through educational game activities at Sekolah Kebangsaan Tanjung Surat, Johor, Malaysia, was designed to enhance three key outcomes: students’ creativity, togetherness, and learning enthusiasm. The intervention was carried out through a series of collaborative educational games (such as word guessing, puzzles, role-play, and team relays) facilitated by cross-country instructors. The implementation results indicated an increase in active participation, positive social interactions among students, as well as the emergence of creative ideas in problem-solving and group presentations. These findings highlight that a structured and contextual play-based learning approach is effective in strengthening students’ intrinsic motivation and socio-cognitive competencies within a multicultural school environment. Recommendations include institutionalizing educational game sessions within the school calendar, conducting joint facilitator training, and establishing periodic evaluations based on creativity, teamwork, and learning engagement indicators.